Keefektifan Konseling Resolusi Konflik untuk Mengatasi Konflik Interpersonal pada Siswa Sekolah Menengah Atas - Budi Purwoko; Johana E. Prawitasari; Adi Atmoko; Dany M. Handarini (Jurnal Pendidikan Humaniora, 2016)
Abstract: This research examined the effectiveness of conflict resolution counseling to solve student’s interpersonal conflict in senior high school. The experimental study used randomized controlled trials design with triple blinding include: client as participants, counselors, and pretest-postestt administrator. Participants were 24 students with destructive interpersonal, devided into 12 students in the experimental group and 12 students in the control group. The experimental group received conflict resolution counseling, and the control group received counseling as usual. Based on anacova statistical test indicated the implementing of conflict resolution counseling had improved four indicators effectively include, (1) positive perceptions of the conflict, (2) collaborative attitude in  facing the conflict, (3) constructive way to resolve conflict, (4) the results of a constructive conflict resolution, and  (5) the combination of four indicators. It can be concluded that, conflict resolution counseling can help the students of senior high school to solve their interpersonal conflicts.Key Words: Conflict resolution counseling, interpersonal conflict, senior high school students                                                                                                                          Abstrak: Penelitian ini menguji keefektifan konseling resolusi konflik untuk menyelesaikan konflik interpersonal pada siswa Sekolah Menengah Atas. Rancangan penelitian menggunakan randomized controlled trials: triple blinding. Subjek penelitian sebanyak 24 siswa dengan konflik interpersonal berpola “menang-kalah” ataupun “kalah-kalah”. Mereka terbagi dalam 12 siswa pada kelompok eksperimen serta 12 siswa pada kelompok kontrol, melalui random allocation. Siswa kelompok eksperimen dikenai konseling resolusi konflik, sedangkan siswa kelompok kontrol dikenai konseling sebagaimana biasa. Berdasarkan uji statistik ancova, diketahui bahwa konseling resolusi konflik dapat meningkatkan (1) persepsi positif terhadap konflik, (2) sikap kolaboratif menghadapi konflik, (3) cara menyelesaikan konflik dengan konstruktif, serta (4) hasil penyelesaian konflik yang konstruktif. Kesimpulannya, konseling resolusi konflik efektif menyelesaikan konflik interpersonal pada siswa SMA, dibandingkan dengan konseling sebagaimana biasa. Berdasarkan hasil penelitian disarankan, bahwa konselor sekolah dapat menggunakan konseling resolusi konflik untuk menyelesaikan konflik interpersonal siswa.Kata Kunci: Konseling resolusi konflik, konflik interpersonal, siswa sekolah menengah atas